Modelling and control of a medium-duty hybrid electric truck. (7th October 2004) - Lin, C.-C.; Filipi, Z.; Louca, L.; Peng, H.; Assanis, D.; Stein, J.
The main contributions of this paper are the development of a forward-looking hybrid vehicle simulation tool, and its application to the design of a power management control algorithm. The hybrid electric vehicle simulation tool (HE-VESIM) was developed at the Automotive Research Center of the University of Michigan to study the potential fuel economy and emission benefits of the parallel hybrid propulsion system for a medium truck. The fundamental architecture of the feed-forward simulation tool and the dynamic equations of its sub-system modules are first described. A power management control algorithm is then designed and evaluated, which is based on mimicking the behaviour of a dynamic-programming optimisation scheme. Simulation results over an urban driving cycle demonstrate that the hybrid control algorithm is able to improve vehicle fuel economy significantly, compared with the original vehicle, powered only by a diesel engine.